Efficiency in Public Education - Staffan Waldo (Lund University, School of Economics and Management, Department of Economics, 2002)
The purpose of the paper is to investigate the influence on efficiency in public education from teacher characteristics and private school competition. Using Data Envelopment Analysis (DEA) an efficiency model introduced by Olesen and Petersen (1995) is extended to include the production environment of the schools. This increases the number of dimensions in the DEA why the possibility to discriminate between production units using educational data is discussed. Efficiency is estimated for 851 of Sweden's approximately 1000 secondary schools in 1994/95. Estimated efficiency implies that the schools can use 9-19% less resources on average, still achieving the same results. The efficiency scores are used as dependent variable in a Tobit regression model. Our primary finding is that competition from private schools has a positive influence on the efficiency in public education but that the teacher characteristics do not significantly explain any efficiency differences.
Keywords: I21; 330; Data Envelopment Analysis; Education